(untitled) (Kinesiology, 2018)
The present study aspires to elaborate on the conceptual framework of flow by further elucidating integration and conceptualization of a relationship between flow and objective and subjective measures of performance. The aims of the study were twofold: (1) to examine the relationship between flow and its key correlates, anxiety, motivation, and perceived ability; (2) to assess whether the relationship between these measures and performance is direct or mediated. Participant sample included a group of cricketers with varying performance level (n = 40) and a group of 20 non-cricket team athletes; all were between 18 and 35 years of age. Their performance was assessed objectively by batting average, along with administering the Dispositional Flow Scale (DFS), Sport Anxiety Scale (SAS), Sport Motivation Scale (SMS), and Perceived Sport Ability (PSA) questionnaires. Results show that the three flow correlates accounted for 77% of dispositional flow variance; individual correlates varied, however, in their predicting power, anxiety: 0%; motivation: 1%; perceived ability: 57%. In addition, total flow and flow correlates accounted for a total of 54% of variance in performance, whereas unique variance of 8% was accounted for by anxiety and perceived ability, each. Notably, flow and two correlates, anxiety and perceived ability, were found to have a direct impact on performance; in contrast, a weak partial mediation of flow was found between motivation and performance. Based on the findings on the flow-performance relationship, expansion of the flow theory is suggested; benefits for advancing intervention research in sport psychology are discussed.